2022
DOI: 10.1007/s12015-022-10490-1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Undernutrition Induces Cell Signalling and Metabolic Dysfunction in Undifferentiated Mouse Embryonic Stem Cells

Abstract: Peri-conceptional environment can induce permanent changes in embryo phenotype which alter development and associate with later disease susceptibility. Thus, mouse maternal low protein diet (LPD) fed exclusively during preimplantation is sufficient to lead to cardiovascular, metabolic and neurological dysfunction in adult offspring. Embryonic stem cell (ESC) lines were generated from LPD and control NPD C57BL/6 blastocysts and characterised by transcriptomics, metabolomics, bioinformatics and molecular/cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…This remarkably short period of protein restriction reduced BCAA levels in blastocysts and blocked glucose metabolism, the primary energy source at this stage. In embryonic stem cells cultured from G3.5 blastocysts, MAPK (mitogen-activated protein kinase), ERK1/2 (extracellular signal-regulated kinase), and mTORC1 (mechanistic target of rapamycin complex 1) signaling pathways were dysregulated ( 92 , 93 ). Cell-tracing and immunohistochemical studies up to G12 showed reduced progenitor proliferation coupled with increased neuronal differentiation in the basal ganglia and cortex.…”
Section: The Role Of Sex and Timingmentioning
confidence: 99%
“…This remarkably short period of protein restriction reduced BCAA levels in blastocysts and blocked glucose metabolism, the primary energy source at this stage. In embryonic stem cells cultured from G3.5 blastocysts, MAPK (mitogen-activated protein kinase), ERK1/2 (extracellular signal-regulated kinase), and mTORC1 (mechanistic target of rapamycin complex 1) signaling pathways were dysregulated ( 92 , 93 ). Cell-tracing and immunohistochemical studies up to G12 showed reduced progenitor proliferation coupled with increased neuronal differentiation in the basal ganglia and cortex.…”
Section: The Role Of Sex and Timingmentioning
confidence: 99%
“…The latter is considered a compensatory mechanism to increase histotrophic nutrition during episodes of protein deprivation and can be induced in vitro by deficient BCAA availability, especially isoleucine (Caetano et al, 2021). There is also evidence of deficiencies in MAP kinase signalling associated with increased apoptosis, and in glycolysis affecting energy metabolism in embryonic stem cell lines derived from maternal protein restricted ICMs (Khurana et al, 2023).…”
Section: Induction Of Altered Developmental Programming By Malnutriti...mentioning
confidence: 99%